(3GdOQ GdCYdi hGdcfR GdCZdis - (3GdMGJej, GdWGFj, GHf YQHj, eMjj GdOjf, eMeO Hf Ydj Hf eMeO Hf YQHj, J(B638(3g`s
(3ChdgG (B:s
(3Gddge jG Mj jG bjhe Hc JMUfJ aGMefj HMeGjI caGjI hbGjI MbjbI HQgGfs
(3BNQgG (B:s
(3hedcG aj GdaQOhS cHjQG hUdi Gddg Ydi SjOfG eMeO hYdi Bdg hUMHg hSde JSdjeG hGdMeO ddg QH GdYGdejf Ke JbQC ShQI (B((3Cde fTQM(B) (3KdGK eQGJs
(3GdJhKjbGJ GdeQLYjI (B:s
(3GdCYdGe(B: 6 / 281s
(3eYLe GdeDdajf(B: 3 / 531s
(3eUOQ GbJfGA GdCUd (B:s
(3OGQ GdcJH GdbWQjIs
(3ehGUaGJ GdhYGA (B:s
Keywords: (3GdJUha hGdBOGH GdTQYjIs